ANÁLISIS DE LA APLICACIÓN WEB DE SOLICITUDES Y RECLAMOS EN LA CORPORACIÓN NACIONAL DE ELECTRICIDAD(CNEL-EP) AGENCIA VINCES - ARREAGA FAJARDO, JOSÉ EDUARDO (2019)
Nowadays, the advancement of technology has found a better way to learn about all the services and benefits that public and private companies provide. Those in need of renewing and developing their productivity must make their products and / or services known to those interested, for which purpose it is intended to create useful applications with simple and friendly interfaces for those who will use it. Through the present case study, the aim is to analyze the web application of the National Electricity Corporation (Cnel.-EP) Agencia Vinces, in its application and claim modules, helping to efficiently manage customer service. With the planting of the problem, it was discovered that in the agency Cnel.-EP of Vinces when carrying out the processes of the requests of the clients and complaints the application usually hangs up due to the great demand of these, on the part of the clients, whether these to complain, for invoiced value, delay of field work, power cuts, meter changes, new service, among other issues related to electric service. Causing that there are economic and time losses in the clients, it is also worth mentioning that, since these modules do not work correctly, the clients tend to congregate in the corridors of the agency that go through some procedure to be carried out. The web application is a necessary tool that provides a positive way to streamline the process and reduce the time lost by customers when approaching to perform some management, but due to the malfunction of these services requests and claims, they are forced to approach that Company. Likewise, the computer application will improve the development of the activities of the company functioning properly and this way contribute in a positive way.